A pilot study of a novel dual - pulsed 1064 nm Q-switched Nd: YAG laser to treat Riehl's melanosis. (December 2014) - Chung, Bo Young; Kim, Jeong Eun; Ko, Joo Yeon; Chang, Sung Eun
Abstract: The treatment of Riehl's melanosis is difficult and challenging. Recently, a low-fluence 1064-nm quality (Q)-switched neodymium: yttrium-aluminum-garnet (Nd: YAG) laser method, referred to as 'laser toning', has been used in the treatment of melasma in Asian countries. We present here a series of cases of Riehl's melanosis that were treated effectively with a novel Q-switched Nd: YAG laser that was operated as a dual-pulse at half-fluence and 140-μs intervals.